Iron status among under-five children with first febrile convulsion and subsequent febrile convulsion - Krishnan, Rekha; S, Geetha; K E, Elizabeth; A N, Anisha (Indian Journal of Child Health, 2018)
Objective: The objective of this study is to estimate the iron status using hemoglobin (Hb), red cell indices, serum iron, plasma ferritin, total iron binding capacity (TIBC), and transferrin saturation (TSAT) in children with first febrile convulsion (FFC) and subsequent FC (SFC). Methods: The study was conducted in a tertiary care teaching hospital among children aged 6 months–5 years with first and subsequent episodes of the simple FC taking cases and controls in a ratio of 2:2:1. Consecutive cases and concurrent controls were selected for the study. Controls were children of the same age group with short febrile illness but without any seizures. After informed consent from parents, detailed history was taken; clinical examination and blood investigations were done to estimate iron status in both cases and controls. Laboratory tests included Hb, hematocrit( Hct), red cell indices, peripheral smear, red cell distribution width (RDW), serum iron concentration, plasma ferritin, TIBC, and TSAT. The data were then analyzed statistically using SPSS software. Results: 44 cases with FFC, 44 with SFC, and 22 controls were included in the study. The mean Hb, Hct, red cell indices, and RDW between the three groups did not show any significant difference. The mean serum ferritin was significantly lower in the SFC group compared to the control group (p=0.005). The mean serum TIBC was significantly higher in the SFC group compared to the control group (p=0.004) and also the SFC group compared to the FFC group (p=0.022). Conclusions: Poor iron status in subsequent febrile seizures indicates that iron deficiency is associated with subsequent seizures. Hence, screening for iron status rather than Hb level estimation should be considered for children presenting with or at high risk for febrile seizures.